La legalità penale nella morsa dell’emergenza Coronavirus (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
The article analyzes the problematic relationship between “pandemic neo-emergency” and the principle of legality in criminal law. In particular, the article examines some significant violations of the principle of criminal legality and focuses on the risks related to the so-called “online process”, in the hope that the coronavirus will not also ‘infect’ our Constitution
Keywords: CoViD-19; pandemic emergency; principle of legality; quarantine; online process